Renewable energy : a concise guide to green alternatives - Carless, Jennifer (New York : Walker, 1993)
Discusses the availability, advantages, and environmental aspects of such alternative energy sources as solar power, wind energy, and hydropower.
Includes bibliographical references (p. 145-162) and index.
Keywords: Renewable energy sources -- United States -- Juvenile literature; Renewable energy sources; Power resources